Is Surgery a Risk in Recovered COVID-19 Patients? - Tosun, Yasin; Akıncı, Ozan; Akdoğan, Osman (Cerrahpaşa Medical Journal, 2021)
Objective: Preoperative evaluation and operation timing have always been a critical aspect of safe surgical practice, and in the midst of the SARS-CoV-2 pandemic, it has become even more crucial to patient safety. The aim of this study is to examine the reliability and results of surgery in recovered COVID-19 patients. Methods: Patients who recovered after COVID-19 infection and who underwent surgery between June 2020 and January 2021 were included in the study. Demographic data of patients, comorbidities, symptoms of COVID-19, time from diagnosis of COVID-19 to surgery (weeks), type of surgery (major/minor), hospitalization time, and postoperative complications were examined. Results: Of the 70 patients, 36 were female and 34 were male. The mean age was 53.7. The number of cases who had asymptomatic and symptomatic COVID-19 infection was 23 and 47, respectively. The interval between infection and surgery was an average of 10.2 (range, 2-31) weeks. The number of major and minor surgical procedures was 54 and 16, respectively. The average hospitalization time was 2.38 days, and 30-day mortality was 1.4%. According to the Clavien–Dindo classification, 61.4% of patients did not develop postoperative complications. There was no significant difference in hospitalization time, Clavien–Dindo score, and mortality between patient groups that had symptomatic and asymptomatic infection (P > .05). There was also no statistically significant correlation between COVID-19 positive diagnosis and postoperative complications, Clavien–Dindo score, and mortality (P > .05). Conclusion: Surgical procedures can be performed safely in recovered COVID-19 patients who do not have symptoms during the time of surgery. İyileşen COVID-19 Hastada Ameliyat Bir Risk midir? Amaç: Preoperatif değerlendirme ve operasyon zamanlaması her zaman güvenli cerrahi pratiğin kritik bir yönü olmuştur ve SARSCov- 2 (COVID 19) pandemisinin ortasında hasta güvenliği için daha da önemli hale gelmiştir. Bu çalışmanın amacı iyileşen COVID-19 hastalarında cerrahinin güvenilirliğini ve sonuçlarını incelemektir. Yöntem: COVID-19 enfeksiyonu sonrası iyileşen, Haziran 2020 – Ocak 2021 tarihleri arasında opere olan hastalar çalışmaya dahil edildi. Hastaların demografik verileri, komorbiditeleri, COVID-19 semptomları, COVID-19 tanısından ameliyata kadar geçen süre (hafta), cerrahi tipi (major/minor), hastanede yatış süresi, postoperatif komplikasyonları değerlendirildi. Bulgular: Hastaların 36’sı kadın, 34’ü erkek, yaş ortalaması 53,7 idi. Olguların 23’ü COVID-19’u asemptomatik, 47’si semptomatik geçirmişti. Enfeksiyon ile ameliyat arasındaki interval ortalama 10,2 (range 2-31) hafta idi. Major ve minor cerrahi prosedürler sırasıyla 54 ve 16 idi. Ortalama hastane yatış süresi 2,38 gün, 30-days mortalite %1,4’tü. Clavien-Dindo sınıflamasına göre hastaların %61,4’ünde postoperatif komplikasyon gelişmedi. Enfeksiyonu semptomatik ve asemptomatik geçiren gruplar arasında hastane yatış süresi, Clavien- Dindo skoru ve mortalite açısından anlamlı bir fark gözlenmedi (P > ,05). COVID-19 pozitif teşhisinden ameliyata kadar geçen süre ile postoperatif komplikasyonlar, Clavien-Dindo skoru ve mortalite arasında da istatistiksel anlamlı bir ilişki bulunmadı (P > ,05). Sonuç: Operasyon sırasında semptomu olmayan iyileşmiş COVID-19 hastalarda cerrahi prosedürler güvenle yapılabilir. Cite this article as: Tosun Y, Akıncı O, Akdoğan O. Is surgery a risk in recovered COVID-19 patients? Cerrahpaşa Med J. 2022. 46(1):30-34.